Clinical and Imaging Features of Familial and Sporadic Multiple Sclerosis - Kamal AmirAshjei Asalemi; Alia Saberi; Amirreza Ghayeghran; Sima Fallah Arzpeyma; Sharareh Eskandarieh; Mohammad Ali Sahraian; Hamidreza Hatamian; Kasra Sarlak; Negin Ashoori; Nima Broomand Lomer (Caspian Journal of Neurological Sciences)
Background: Multiple sclerosis (MS) is a demyelinating neurodegenerative disease affecting the central nervous system (CNS). While most cases are sporadic, familial MS (FMS) constitutes approximately 12.6% of the MS population and is characterized by affected family members. This study aims to investigate the difference between clinical and radiological findings of patients with FMS and sporadic MS (SMS) living in Guilan Province, Iran. Materials & Methods: In this cross-sectional study, by evaluating their medical records, we examined 113 patients with SMS and 79 patients with FMS who registered in the nationwide MS registry of Iran (NMSRI)-Guilan. The radiologic data were analyzed using OsiriX software, version 12.0. Results: Compared to the FMS group, the SMS group showed significantly higher age at onset (31.48±9.55 vs 28.92±9.46, P=0.034), higher occurrence of diplopia (29.2% vs 16.4%, P=0.042), higher expanded disability status scale (EDSS) score (2.20±2.61 vs 1.09±2.08, P=0.002), more lesions (31.59±25.36 vs 22.83±17.17, P=0.017), higher frequency of lesions in the periventricular region (98.2% vs 89.8%, P=0.017) and the lower average size of the smallest lesions (4.65±2.57 vs 8.12±8.58, P<0.001). EDSS score showed significant associations with type of MS (SMS or FMS) (β=0.78, P=0.016), onset age (β=0.09, P<0.001) and disease duration (β=0.13, P=0.001). Conclusion: FMS differs from SMS with an earlier onset, predominantly relapsing-remitting phenotype, lower diplopia incidence, lower EDSS scores, fewer periventricular lesions and larger smallest lesions.